Peningkatan Motivasi Belajar Siswa melalui Project Based Learning pada Mata Pelajaran Biologi Kelas XI IPA di SMA Negeri 1 Parigi Utara - Nurfatia Nurfatia; Mohammad Jamhari; Yulia Windarsih; Lilies Lilies; Rafiqa Rafiqa; Amalia Buntu (Bioed : Jurnal Pendidikan Biologi, 2026)
This research is motivated by the low learning motivation of class XI IPA 2 students at a high school in Parigi Moutong Regency in the subject of Biology, which is characterized by passive participation and lack of interaction during the learning process. The aim of this research is to increase student learning motivation through the application of the Project Based Learning (PjBL) model. The method used is Classroom Action Research (CAR) conducted in two cycles, covering the stages of planning, action, observation, and reflection. The research subjects consisted of 22 students. Data collection instruments used observation sheets for teacher activities and student learning motivation which were analyzed descriptively quantitatively. The research results showed a significant increase in student learning motivation, from an average of 59% (fair category) in cycle I to 78% (high category) in cycle II. The conclusion of this research is that the application of the Project Based Learning model is effective in increasing student learning motivation in Biology subjects. The implication is that this model can be used as a reference for teachers to create a more active, creative, and collaborative learning atmosphere.Keywords: Biology, Learning Motivation, Project Based Learning.